Thermodynamic analysis of the formation reaction of second phases in Mg–Zn–Mn–Sn–Nd alloys. Issue 3 (11th February 2017) - Hu, G.; Xing, B.; Huang, F.; Zhong, M.; Zhang, D.
Abstract : The thermodynamic characteristics and solidification sequence of Mg–6Zn–1Mn–4Sn– x Nd ( x  = 0.5, 1.0, 1.0, wt-%, ZMT614- x Nd) alloys were investigated using CALPHAD, Miedema model, differential scanning calorimetry and transmission electron microscopy (TEM) analysis. The results revealed that the as-cast ZMT614-Nd alloys consisted of α-Mg, Mn, Mg7 Zn3, Mg2 Sn and MgSnNd phases. Owing to its higher phase transition temperature and lower formation enthalpy, MgSnNd phase formed first during the casting process. The formation of MgSnNd phase consumed all Nd elements, which restrained the formation of other Nd-containing phases. As a result, the solidification sequence of ZMT614-1.5Nd alloy was α-Mg → MgSnNd → Mn → Mg2 Sn → Mg7 Zn3 . TEM analysis suggested that the MgSnNd phase had a low-symmetry crystal structure.